Substardand practices of adjustment measurements in local geodetic networks - Silvia Gašincová; Juraj Gašinec (Acta Montanistica Slovaca, 2005)
Various instruments and measuring techniques are serviceably combined in geodetic networks. The sets of measured data have a disunited physical character and quality. At the positional geodetic networks are associated angular, length, GPS or other kinds of measurements. If the solver of a geodetic task wants to comprehend the influence of the measured data quantities errors on the results of the estimating process, it is necessary to transform the heterogenity of measurements in the calculating space to one physical dimension in which the human mind orientates more easily and finds the internal connections and the valid regularities arising among components of geodetic network mutually as well the status of physical environs in which the measurement was realized. In this paper,for the measured directions is proposed an original mediating quantity the oriented curved distance and it is confronted with the corresponding standard mediating quantities to which the measured directions are transformed. By solving of practically measured networks it was evidenced that the oriented curved distance conduces to identical results. However, as a metric quantity, it more objectively informs the solver of a geodetic task about mistake proportions in the target points and about their quality. By their analysis it is possible to appreciate more easily an influence of particular kinds of measurements on the estimated parameters quality.